Polyphony in the brothers Karamazov: Christian dialogical tension in Alexei Fyodorovich Karamazov'S interactions - Silistino, Davi [UNESP] (My University, 2015)
This work's aim is to analyze polyphony in The Brothers Karamazov, a novel written by Fyodor Dostoevsky, focusing on ideological confrontations that take place between characters, especially between the Karamazov's family. More specifically, I try to understand how Alexei Fyodorovich Karamazov interacts in a dialogical way with his family and friends, and how Alexei's interventions - marked by a religious ethical behavior - contribute to the conflicting discourses. To do so, the main concept on which this paper is relied is the polyphony, developed by Bakhtin in order to understand that each character in the book has a strong and distinct ideology, which helps creating tensions of immense proportions. Finally, this study is also based on Nietzsche's theories about religion, because it is argued that some characters are guided by a Christian ethical thinking, which is - although shown as good most of the times - surrounded by an oppressive fundamentalism.
Keywords: Dostoevsky; Polyphony; Russian literature; The Brothers Karamazov